Humour In R K Narayan’S Swami and Friends: Exploring the Impact of Humour and Laughter in R K Narayan’s Swami and Friends (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Humour andlaughter are the greatestvirtues that God has bestowedon man. A sense of humour makes one see one‟s proper place in this world, and teaches him tosee things in proportion.  Both  humour  and  laughter  are  universal,  though  there arenational  differences  on  certain  aspects.  Theyhave their place in all arts andtheir enjoyment leadsto aesthetic experience ofa unique kind.